2004
DOI: 10.1002/cne.20159
|View full text |Cite
|
Sign up to set email alerts
|

Pretectal and tectal afferents to the dorsal lateral geniculate nucleus of the turtle: An electron microscopic axon tracing and γ‐aminobutyric acid immunocytochemical study

Abstract: The pretectal and tectal projections to the dorsal lateral geniculate nucleus (GLd) of two species of turtle (Emys orbicularis and Testudo horsfieldi) were examined under the electron microscope by using axonal tracing techniques (horseradish peroxidase or biotinylated dextran amine) and postembedding gamma-aminobutyric acid (GABA) immunocytochemistry. After injection of tracer into the pretectum, two types of axon terminals were identified as those of pretectogeniculate pathways. Both contained pleomorphic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 107 publications
0
8
0
Order By: Relevance
“…In reptiles an entirely comparable GABAergic pathway has been demonstrated in the turtle (Kenigfest et al, 2000(Kenigfest et al, , 2004. It arises in the nucleus lentiformis mesencephali and to a lesser extent in the nuclei griseus tectalis and pretectalis ventralis.…”
Section: Extrinsic Axonsmentioning
confidence: 64%
See 4 more Smart Citations
“…In reptiles an entirely comparable GABAergic pathway has been demonstrated in the turtle (Kenigfest et al, 2000(Kenigfest et al, , 2004. It arises in the nucleus lentiformis mesencephali and to a lesser extent in the nuclei griseus tectalis and pretectalis ventralis.…”
Section: Extrinsic Axonsmentioning
confidence: 64%
“…It arises in the nucleus lentiformis mesencephali and to a lesser extent in the nuclei griseus tectalis and pretectalis ventralis. In birds, the nuclei lentiformis mesencephali (pars magnocellularis and parvocellularis), griseus tectalis and principalis precommissuralis also project to the DLL (Gamlin and Cohen, 1988;Wild, 1989;Wylie et al, 1998); however, the GABAergic nature of this second pretectothalamic pathway, while highly probable (Kenigfest et al, 2000(Kenigfest et al, , 2004, has not been conclusively demonstrated by double labeling. The role played by the ascending GABAergic projection from the pretectal nuclei to the GLd/DLA is far from completely elucidated, although the involvement of the pretectum in visuomotor function and the integration of visual sensory and oculomotor function has been demonstrated in several studies (cf.…”
Section: Extrinsic Axonsmentioning
confidence: 97%
See 3 more Smart Citations